Prosocial behavior among human workers in robot-augmented production teams—A field-in-the-lab experiment - Gorny, Paul M.; Renner, Benedikt; Schäfer, Louis (Frontiers in Behavioral Economics, 2023)
Human-machine interaction has raised a lot of interest in various academic disciplines, but it is still unclear how human-human interaction is affected when robots join the team. Robotics has already been integral to manufacturing since the 1970s. With the integration of AI, however, they are increasingly working alongside humans in shared spaces. We conducted an experiment in a learning factory to investigate how a change from a human-human work context to a hybrid human-robot work context affects participants' valuation of their production output as well as their prosociality among each other. Learning factories are learning, teaching, and research environments in engineering university departments. These factory environments allow control over the production environment and incentives for participants. Our experiment suggests that the robot's presence increases sharing behavior among human workers, but there is no evidence that rewards earned from production are valued differently. We discuss the implications of this approach for future studies on human-machine interaction.